2014
DOI: 10.1016/j.foodcont.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptability of interventions to reduce Campylobacter in the poultry food chain

Abstract: Reducing human Campylobacter cases has become a priority for the UK Government. However the public's views on acceptability of interventions to reduce Campylobacter in poultry production are poorly understood in the UK and in other countries around the world. The objective of the study was to investigate how increasing awareness and knowledge changes consumer acceptability of interventions that reduce human campylobacteriosis in the poultry food chain. This approach is readily applicable to other risks and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…A recent study evaluated consumer acceptability through a printed survey (MacRitchie et al . ), which revealed that irradiation or chemical treatment of chicken meat are the least acceptable measures, even if they could decrease human campylobacteriosis cases by 90%. In contrast, better hygiene practices on farms are the most acceptable to consumers.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study evaluated consumer acceptability through a printed survey (MacRitchie et al . ), which revealed that irradiation or chemical treatment of chicken meat are the least acceptable measures, even if they could decrease human campylobacteriosis cases by 90%. In contrast, better hygiene practices on farms are the most acceptable to consumers.…”
Section: Resultsmentioning
confidence: 99%
“…The main objective of this paper was to produce cost estimates that can be used to evaluate various policy interventions that affect the level of food safety. Various potential interventions have been suggested for different stages of the food supply chain [ 76 ]. At the farm level, possible risk-reducing measures include using boot dips or fly screens, or to disinfect equipment and vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Shigella and Salmonella could contaminate similar types of samples, thus it would be significant to simultaneously identify the two pathogens (Li and Mustapha, 2004 ; MacRitchie et al, 2014 ). Culture-based techniques and biochemical are the most common detection assays, while require a long enrichment time and subsequent identification (Mokhtari et al, 2012 ; Soria et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%